THE ANIMAL IN THE DEITY: VISAYAN GODS AND GODDESSES AND THEIR ANIMALS - Michael Angelo Mahinay; Fely Bukiron Latras (Universitas Muhammadiyah Surakarta, 2019)
This study aimed to investigate the unconscious connection between the Visayan gods and goddesses and their sacred animals based on the archives of Felipe Landa Jocano’s Outline of Philippine Mythology, Francisco Demeterio’s Towards a Survey of Philippine Folklore and Mythology, and Luzviminda’s blog Visayan Mythologies of the Philippines. The psychoanalytical frameworks of totemism and the collective unconscious drew connections that delineated the cultural symbolism of the animal to its respective deity and linked it further to the values and spheres each deity imparts on the communities that worship it. Through the lens of this theoretical approach, a deep, direct nature of association was extracted between the gods and their sacred animals. Thus, the pre-colonial Visayan communities viewed their animal neighbors as manifestations or totems of divine power that in turn, governs their affairs. An animal that was defined as sacred formed a very essential component of a deity’s identity, and, in consequence, the identity of his or her mortal believers.